Patterned Substrate of Mobile and Immobile Ligands to Probe EphA2 Receptor Clustering - Zhongwen Chen (770401) (2022)
A multitude of membrane-localized receptors are utilized by cells to integrate both biochemical and physical signals from their microenvironment. The clustering of membrane receptors is widely presumed to have functional consequences for subsequent signal transduction. However, it is experimentally challenging to selectively manipulate receptor clustering without altering other biochemical aspects of the cellular system. Here, we describe a method to fabricate multicomponent, ligand-functionalized microarrays, for spatially segregated and simultaneous monitoring of receptor activation and signaling in individual living cells. While existing micropatterning techniques allow for the display of fixed ligands, this protocol uniquely allows for functionalization of both mobile membrane corrals and immobile polymers with selective ligands, as well as microscopic monitoring of cognate receptor activation at the cell membrane interface. This protocol has been developed to study the effects of clustering on EphA2 signaling transduction. It is potentially applicable to multiple cell signaling systems, or microbe/host interactions. Other Information Published in: BIO-PROTOCOL License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.21769/bioprotoc.4434